Exploring experiences of implementing standardized cancer patient pathways within investigatory units - a qualitative study - Jeanette Winterling; Sara Delilovic; Jessica Dervish; Malin Gunarsson; Mårten Åhström; Henna Hasson (BMC, 2021)
Abstract Background In the implementation of standardized cancer patient pathways (CPPs), the investigatory units, endoscopy, radiology and pathology, are crucial to ensure an eventual cancer diagnosis. However, when evaluating the implementation of CPPs, little attention has been paid to the healthcare professionals working in these units. The aim of this study was to explore experiences of the implementation of CPPs among health professionals in investigatory units. Methods This descriptive qualitative study included 55 health professionals working in investigatory units. Participants were interviewed in 2017-2018, and data were analysed using thematic analysis. Results The health professionals reported benefits, facilitators and challenges when describing their experiences of implementing CPPs. Benefits included that CPP improved collaboration and increased focus on the patients. Facilitators in the implementation process included pre-existing well-functioning work processes and having supportive functions (e.g. coordinators). Challenges included the lack of staff and clinical equipment, as well as unjustified time-slots and incorrect referrals. Conclusions The findings show that most health professionals working in investigatory units' experience benefits with the implementation of CPP, but the lack of resources was especially hard to overcome.